2015
DOI: 10.1111/mice.12135
|View full text |Cite
|
Sign up to set email alerts
|

Performance‐Based Probabilistic Capacity Models and Fragility Estimates for RC Columns Subject to Vehicle Collision

Abstract: With the increasing population and the demand associated with it, the infrastructure and transportation facilities have increased rapidly over the years. The progress has been accompanied by an increasing number of vehicle collisions with structures. This type of collision might lead to the damage and sometimes collapse of the structures. In reinforced concrete (RC) structures, columns are usually the most vulnerable members exposed to collisions. However, the existing design guidelines and provisions for prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Furthermore, Sharma et al (2015) established probabilistic shear capacity models for each performance level based on Bayesian inference method and extensive FE simulations. Combined with the corresponding probabilistic shear force demand model (Sharma et al, 2014), the vulnerability of the RC columns were analyzed (Sharma et al, 2015). Do et al (2019aDo et al ( , 2019b, respectively, proposed semi-empirical formulas for calculating dynamic shear capacity and sectional force demand (shear and bending moment) of RC columns under vehicle collision based on FE simulations, and finally established a force-based damage assessment method.…”
Section: Force-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Sharma et al (2015) established probabilistic shear capacity models for each performance level based on Bayesian inference method and extensive FE simulations. Combined with the corresponding probabilistic shear force demand model (Sharma et al, 2014), the vulnerability of the RC columns were analyzed (Sharma et al, 2015). Do et al (2019aDo et al ( , 2019b, respectively, proposed semi-empirical formulas for calculating dynamic shear capacity and sectional force demand (shear and bending moment) of RC columns under vehicle collision based on FE simulations, and finally established a force-based damage assessment method.…”
Section: Force-based Methodsmentioning
confidence: 99%
“…Sharma et al (2012) defined three performance levels (corresponding to four damage levels) for RC columns under vehicular impact, and determined the shear capacity of the columns for each performance level to be the maximum value of the sectional shear force when the corresponding damage features were reached. Furthermore, Sharma et al (2015) established probabilistic shear capacity models for each performance level based on Bayesian inference method and extensive FE simulations. Combined with the corresponding probabilistic shear force demand model (Sharma et al, 2014), the vulnerability of the RC columns were analyzed (Sharma et al, 2015).…”
Section: Damage Assessment Of Rc Pier Under Vehicle Collisionmentioning
confidence: 99%
“…To estimate the element damage, a limit state function g is evaluated, where the capacity corresponding to each damage state is compared with the EDPs obtained from the structural analysis component. Recent efforts have been devoted to the probabilistic characterization of structural element capacities (Gardoni et al, 2002;Choe et al, 2008;Sharma et al, 2015), however, these can be defined as deterministic if the information on the variability of the capacity is not available, comes at a large computational cost, or is deemed relatively known. The vector of engineering capacity parameters (ECPs) is then defined as:…”
Section: Damage Analysismentioning
confidence: 99%
“…The results showed that the present collision design codes could be conservative and the bridge columns were vulnerable to impact loadings, so the effect of them should be considered in design procedure [3,4]. In following, probabilistic framework is proposed by Sharma et al (2014Sharma et al ( , 2015 for the assessment of dynamic shear force capacity and demand of reinforced concrete (RC) columns subjected to vehicle impact using fragility curves [5,6]. Also, the effects of different foundation connection details are investigated by Kang and Kim (2017) on performance of a steel column under vehicle impact.…”
Section: Introductionmentioning
confidence: 99%